Persistent erythema multiforme associated with Epstein–Barr virus infection. (7th December 2013) - Turnbull, N.; Hawkins, D.; Atkins, M.; Francis, N.; Roberts, N.
Summary Erythema multiforme (EM) is a common, self‐limiting condition. Recurrent EM is a well‐recognised variant, often associated with herpes simplex virus infection. It is frequently managed with prophylactic aciclovir. Anecdotal reports suggest that recurrent EM may be associated with the use of corticosteroids. Persistent EM, however, is a rare variant, with few cases reported in the literature. It has a protracted course often with atypical and inflammatory lesions. It has been associated with occult viral infections, particularly Epstein–Barr Virus (EBV), as well as inflammatory bowel disease and malignancy. We report a case of EM associated with EBV infection.